Regulating Scientific Diving and Underwater Archaeology: legal and historical considerations. (30th October 2015) - Benjamin, Jonathan; MacKintosh, Robert
Abstract : The regulation of scientific and archaeological diving is complex but it is essential that underwater archaeologists are familiar with the requirements placed on them by legal systems. This paper outlines the history and development of current legal systems in four jurisdictions: the UK, USA, EU and Australia. This historical and legal approach informs key discussions facing maritime archaeologists; reference is made to training requirements, safety records and the question of who should be allowed to participate and who should be excluded from archaeological diving.